Sistem Pungutan Denda Pajak Kendaraan Bermotor di Kantor Samsat Parepare (Persepktif Ekonomi Islam) - Kurniawan, Andis; Semaun, Syahriyah; Arqam (Program Studi Ekonomi Syariah IAIN Parepare, 2023)
This study aims to find out how the mechanism for collecting motor vehicle tax fines at the Samsat Office in Parepare city and to find out how the Islamic economic review of the collection of motor vehicle tax fines at the Samsat Office in Parepare city. The subject matter is then broken down into several sub-problems or research questions, namely how the Parepare Samsat Office determines the amount of motorized vehicle tax for each vehicle, whether all vehicles registered as taxpayers comply with paying taxes, and how to determine tax penalties for late paying. This type of research is qualitative with the approach used is a sociological and economic approach. The data sources for this research are primary data obtained from the Parepare Samsat Office and interviews as well as secondary data from library research. Furthermore, the data collection method was carried out by interviews and documentation for further analysis by reducing data, presenting data, and drawing conclusions. The results of this study indicate that the flow of payment of tax fines at the Parepare Samsat Office is in accordance with the provisions as it should be. In addition, the tax fines used at the Parepare Samsat Office on motorized vehicles are in accordance with the South Sulawesi Governor's Decree, but the tax penalty rules are not in accordance with the principles of Islamic Economics, namely the principle of justice.